8(-X-1)+X=2X+17

Simple and best practice solution for 8(-X-1)+X=2X+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(-X-1)+X=2X+17 equation:


Simplifying
8(-1X + -1) + X = 2X + 17

Reorder the terms:
8(-1 + -1X) + X = 2X + 17
(-1 * 8 + -1X * 8) + X = 2X + 17
(-8 + -8X) + X = 2X + 17

Combine like terms: -8X + X = -7X
-8 + -7X = 2X + 17

Reorder the terms:
-8 + -7X = 17 + 2X

Solving
-8 + -7X = 17 + 2X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-2X' to each side of the equation.
-8 + -7X + -2X = 17 + 2X + -2X

Combine like terms: -7X + -2X = -9X
-8 + -9X = 17 + 2X + -2X

Combine like terms: 2X + -2X = 0
-8 + -9X = 17 + 0
-8 + -9X = 17

Add '8' to each side of the equation.
-8 + 8 + -9X = 17 + 8

Combine like terms: -8 + 8 = 0
0 + -9X = 17 + 8
-9X = 17 + 8

Combine like terms: 17 + 8 = 25
-9X = 25

Divide each side by '-9'.
X = -2.777777778

Simplifying
X = -2.777777778

See similar equations:

| 24-(x+7)=4x-3 | | 16^(3/4) | | -5X+1=-X+3(4-2X) | | -2X+3(4X-8)=7X-3 | | x/4-15=8 | | (x+0.1)(x)=-.00000002 | | 8(5x+4)=6(8x-2) | | =7(2+3x)+8 | | Rg-2n=y | | 29-17=3x-1 | | -2(3z+1)3-10=4 | | 7-3(x-6)=6x-2 | | -2(3z+1)3-150=4 | | -3(1+4k)=3(1-6k) | | 8x-[2x-(5x-5y)]-3y= | | b^2+2b-100=0 | | 7=x^1/3 | | 3(X-5)=19 | | 9(8d-5)+15=12d-2 | | 0.06(x*30)+0.27(x+10)=10.8 | | -(-7+2a)=7(1-8a) | | (9x-16)/7=0 | | 12x=11x+23 | | -8x-28+10=-2 | | 7n+35=4n+36 | | 18-3y+11=7y+6y-27-9y | | 7(2-k)+4k=-6(k-6)+5k | | -1/5=x^1/3 | | 3cb-2ba=12 | | 10a=-8a+12 | | -y-8+7y=-9+5y+1 | | 2(5x+8)=x+20 |

Equations solver categories